Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Hasil Belajar Siswa pada Materi Sistem Koordinasi Manusia Kelas XI - Sidelvi Tamu Ina; Yohana Makaborang; Riwa Rambu Hada Enda (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This study aims to improve the learning outcomes of class XI students of SMA Negeri 1 Pahunga Lodu through the application of a jigsaw cooperative learning model assisted by learning videos. This type of research is classified as Classroom Action Research (PTK) which is carried out in two cycles, which consists of four stages, namely: 1) planning; 2) implementation; 3) observation; and 4) the reflection stage. The subjects of this study were 38 students in class XI at SMA Negeri 1 Pahunga Lodu for the academic year 2022/2023, consisting of 14 male students and 24 female students. The data obtained in this study were in the form of student learning outcomes taken from the application of the jigsaw type cooperative learning model assisted by learning videos. The instruments used are: 1) interviews; 2) test; and 3) run. The results of the research and data analysis in cycle I and cycle II revealed that there was an increase in the learning outcomes of class XI students at SMA Negeri 1 Pahunga Lodu for the 2022/2023 academic year. This is indicated by an increase in the proportion of student learning outcomes in biology lessons on human coordination system material. The research results obtained the proportion of student learning outcomes in cycle I was 73%, and cycle II was 92%. The conclusion of this study is that the application of the jigsaw cooperative learning model can improve the learning outcomes of class XI students of SMA Negeri 1 Pahunga Lodu.